Analisis Pengendalian Intern Atas Kredit Pemilikan Rumah Dalam Mencegah Terjadinya Kredit Macet - Rosita, Siti Ita; Nurjanah, Yayuk; Ronald, Ronald (Jurnal Ilmiah Akuntansi Kesatuan, 2015)
One of the bank loan distributions is a loan that was directed at communities in need of housing. In the process of granting the Housing Ownership Loan, each Bank has its own rules and procedures to execute. A standard made to minimize non performing loans. This study was to analyse the role of internal control department in preventing the non preventing loans from happening. The result of this research indicates the effectiveness of the internal control role in the Housing Ownership Loan at Bank Panin. Bank Panin has done the right control. Each year, Bank Panin does some reviews to the internal control in the Housing Ownership Loan, and is always updated to decrease the current bad debts. Keywords: Internal Control, Bad Debt